2013
DOI: 10.1259/bjr.20130290
|View full text |Cite
|
Sign up to set email alerts
|

MDCT features in the differentiation of T4a gastric cancer from less-advanced gastric cancer: significance of the hyperattenuating serosa sign

et al.

Abstract: The hyperattenuating serosa sign is associated with gastric cancer with invading the serosa and can facilitate planning of the optimal pre-operative evaluation and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
1
16
0
1
Order By: Relevance
“…The AJCC proposed preoperative clinical TNM staging to guide attending physicians in making preliminary treatment decisions, but a lack of consistency in the initial clinical evaluation has been documented, including non-standardized radiological reports (5). Kim et al reported that the accuracy of CT in distinguishing T3 and T4 GC was only 60%, similar to the diagnostic accuracy of the traditional model in the present study (ACC: training set, 0.764; test set, 0.750) (18). In a multicenter prospective study, the preoperative clinical stage and postoperative pathological diagnosis of 4,534 cases of GC were compared.…”
Section: Discussionmentioning
confidence: 49%
“…The AJCC proposed preoperative clinical TNM staging to guide attending physicians in making preliminary treatment decisions, but a lack of consistency in the initial clinical evaluation has been documented, including non-standardized radiological reports (5). Kim et al reported that the accuracy of CT in distinguishing T3 and T4 GC was only 60%, similar to the diagnostic accuracy of the traditional model in the present study (ACC: training set, 0.764; test set, 0.750) (18). In a multicenter prospective study, the preoperative clinical stage and postoperative pathological diagnosis of 4,534 cases of GC were compared.…”
Section: Discussionmentioning
confidence: 49%
“…Because of the decreased number of tumor cells, edema, fibrosis, and chronic inflammation after chemotherapy ( 36 ), the blurred border of lesions seriously hinders accurate judgment. By extracting high-throughput quantitative imaging features, radiomics can characterize the spatial relationships and consistency of signal intensities within the tumor region ( 18 ), showing their utility in discriminating serosal invasion in preoperative staging ( 37 , 38 ). In summary, our radiomics models performed well in accurately classifying serosal invasion not only in the training cohort, with AUCs of 0.940, 0.953 and 0.953 for the 120 kVp model, IM-120 kVp model and ComModel, respectively, but also in the testing cohort, with the AUCs of 0.831, 0.879 and 0.914, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of serosa invasion before the surgery has a crucial significance because for locally AGC with serosal invasion, neoadjuvant chemotherapy is being used more frequently to downstage the tumor and treat micrometastases (7,8). Moreover, differentiation between T3 and T4a gastric carcinoma is very important to determine the appropriate procedure of surgery and expect the prognosis, especially for the risk of peritoneal dissemination.…”
Section: Original Articlementioning
confidence: 99%
“…Moreover, differentiation between T3 and T4a gastric carcinoma is very important to determine the appropriate procedure of surgery and expect the prognosis, especially for the risk of peritoneal dissemination. For T4a gastric cancer staging, the reported computed tomography (CT) accuracy varies considerably, ranging from 77.8% to 93.5% (6)(7)(8). The reported CT criteria for T4a gastric cancer are extraluminal extension of the gastric wall and haziness of the perigastric fat (8).…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation